PENDEKATAN GENDER DALAM STUDI ISLAM - Nur Adilah Mahyaddin (SANGAJI: Jurnal Pemikiran Syariah dan Hukum, 2017)
The term of gender became popular until now, it had been caused by critic to the policy in any Europe Countries such as the policy of problem which happen in employ. It to be different between male and female in job. Meanwhile, Islam ranges Female. In this paper, researcher use the theory of gender to see how Islam range female. Event tough Islamic and Positive Low had ranged details, however many females to be object or subordinat in any situation compared males, finally fameless more violent. So, in this situation, researches think the problem is very important to solve, females not only object of violent but they have fitrah (basic right) to be respected. Hopefully, the term of gender must be understanded clearly and done rightly, so there is not conflict caused by misunderstanding about gender